Greatly boosting electrochemical hydrogen evolution reaction over Ni3S2 nanosheets rationally decorated by Ni3Sn2S2 quantum dots - Lu, Shi-Yu; Li, Shengwen; Jin, Meng; Gao, Jiechang; Zhang, Yanning (Applied catalysis. B, Environmental, 2020)
[Display omitted] •Rationally tailor Ni3Sn2S2 QDs-decorated Ni3S2 Nanosheets establish high-surficial multi-heterogeneous catalysis.•Ni3Sn2S2@Ni3S2 can realize both strong water absorption and strong H atom desorption.•The optimized Ni3Sn2S2@Ni3S2 surpass commercial Pt/C toward HER.•The more detailed enhancement mechanism were investigated by combining experimental and theoretical investigations. The electrode kinetics of hydrogen evolution reaction (HER) greatly relies on both strong water absorption and strong H atom desorption for fast electron transfer while prompting hydrogen evolution, but it is very challenging to achieve due to the tough trading off between water absorption and H-desorption ability of the catalyst. Herein, a unique high-surficial multi-heteroatomic catalytic process is realized by rationally design and tailor Ni3Sn2S2 dots-decorated thin Ni3S2 nanosheets to form sheets-on-sheets array self-supported electrode by simple hydrothermal process. The formed Ni3Sn2S2@Ni3S2-2 NF delivers a superior performance very close to the noble catalyst (Pt/C) at low current densities with an onset-potential of nearly 0 mV and overpotentials of 50.7 mV at 10 mA cm−2 while surprisingly surpassing Pt/C at high current densities. The outstanding HER performance of the catalyst can be ascribed that the rationally tuned multi-heterogeneous interfaces and electronic structure control can realize both strong water absorption and strong H atom desorption to not only significantly promotes fast electron transfer, but also greatly enhances the gas release toward efficient HER. This work holds a great promise to fabricate a non-noble HER catalyst for high-performance close to the noble catalysts such as Pt/C while shedding a light on fundamentals to guide construction of high-surficial heteroatomic multi-heterogeneous catalysts with superior performance.